A Study of Articles on Religion in Major Sociology Journals: Some Preliminary Findings - Buehler, Charles (Journal for the scientific study of religion, 1972)
The authors classified articles in the sociology of religion that appeared in five journals from the inception of these journals to 1969. It was found that the proportion of articles about religion has remained more or less constant over the years. There has, however, been a strong trend toward quantitative studies. Over half the quantitative research has dealt with some aspect of individual religiosity, and religious variables have been treated as independent almost as often as they have been treated as dependent. Only about a third of the quantitative articles contain an identifiable theoretical framework, and most of them continue to use rather simple methods of data analysis. Almost none of the articles are longitudinal or cross-cultural.